2023
DOI: 10.4062/biomolther.2022.116
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals That Act on Synaptic Plasticity as Potential Prophylaxis against Stress-Induced Depressive Disorder

Abstract: Depression is a neuropsychiatric disorder associated with persistent stress and disruption of neuronal function. Persistent stress causes neuronal atrophy, including loss of synapses and reduced size of the hippocampus and prefrontal cortex. These alterations are associated with neural dysfunction, including mood disturbances, cognitive impairment, and behavioral changes. Synaptic plasticity is the fundamental function of neural networks in response to various stimuli and acts by reorganizing neuronal structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…The hippocampus is an important region of the limbic system associated with depression and cognitive function ( Jia et al, 2023 ; Yoon et al, 2023 ). Under stimulation of various pathological factors, hippocampal immune cells release large amounts of proinflammatory cytokines that contribute to neuroinflammation, which could increase the risk of depression and cognitive decline ( Wu et al, 2021 ; Hao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus is an important region of the limbic system associated with depression and cognitive function ( Jia et al, 2023 ; Yoon et al, 2023 ). Under stimulation of various pathological factors, hippocampal immune cells release large amounts of proinflammatory cytokines that contribute to neuroinflammation, which could increase the risk of depression and cognitive decline ( Wu et al, 2021 ; Hao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…TSC2 is transcriptionally regulated by p53, activated by AMPK, inhibits the mTOR signaling pathway, and plays a key role in regulating cellular energy metabolism 242,243 . The mammalian target of rapamycin (mTOR), a class of serine/threonine kinases, is an intracellular signaling molecule 244 . Abnormal activation of mTOR signaling can lead to multiple adverse outcomes, including tumor formation, neonatal insulin resistance, and adipogenesis 245 .…”
Section: Regulatory Mechanisms Of P53 On Downstream Genesmentioning
confidence: 99%
“… 242 , 243 The mammalian target of rapamycin (mTOR), a class of serine/threonine kinases, is an intracellular signaling molecule. 244 Abnormal activation of mTOR signaling can lead to multiple adverse outcomes, including tumor formation, neonatal insulin resistance, and adipogenesis. 245 Inactivating mutations in TSC2 cause hamartomas primarily in multiple organ systems.…”
Section: Regulatory Mechanisms Of P53 On Downstream Genesmentioning
confidence: 99%
“…Studies have demonstrated that chronic stress can cause a series of psychological problems, with the cumulative effect of stressors serving as a significant predictor of symptoms associated with depression and anxiety [ [2] , [3] , [4] ]. Prolonged exposure to stress induces neuronal atrophy, which is characterized by synaptic loss and diminished volume in the hippocampus and prefrontal cortices, potentially leading to mood disorders, cognitive impairments, and behavioral alterations [ 5 ]. In addition to chronic stress accumulated over an extended duration, college students also encounter various acute stressful events, such as examinations or emergencies.…”
Section: Introductionmentioning
confidence: 99%